Abdominal Aortic Aneurysm: What About Screening? - Saucy, Francois; Deglise, Sebastien; Holzer, Thomas; Briner, Lukas; Benezit, Marie; Delay, Charline; Kazandjian, Caroline; Corpataux, Jean-Marc (Current Pharmaceutical Design, 2015)
The prevalence of abdominal aortic aneurysm (AAA) in general population is 4-9% with a high mortality rate when ruptured. Therefore, screening programs were developed in many countries to detect small and large AAA in selected patients. Indeed, prevalence of AAA increases in patients over 65 years old with cigarette smoking history. This paper reviews recent literature related to AAA screening focusing on epidemiology, screening tests and evidence based medicine to highlight not only advantages but also disadvantages of screening programs among population.
Keywords: Abdominal aortic aneurysm